Pesca artesanal no Rio Vacacaí, RS: influências da orizicultura irrigada e os potenciais territórios de conflitos - Moraes, Tiago Rossi de (2015)
This research has as its central theme the artisanal fishing practiced in Vacacaí River, RS. In the course of the study it was sought to characterize this activity, identifying its relationship with other economic activities that also use the river water, especially irrigated rice cultivation, from the vision of artisanal fishermen, and with the contribution of bibliographical and documentary research. From information obtained through official data of rice production and planted area, rainfall and altitudes of Vacacaí River, in the years 2004 to 2013, it was established the relationship between excessive consumption of water from irrigated rice cultivation and the decrease in the level of the river, one of the main problems pointed out by fishermen. Through three expeditions in which was traveled over 200 kilometers of Vacacaí Riverbed, where the water level allows navigation, it was mapped 64 rice fields irrigation pumps and another 24 disabled facilities. To identify Vacacaí fishing sites it was used participatory mapping, in which those interviewed artisanal fishermen made the recognition of their fishing grounds with the help of satellite images mosaics. That way seventeen fishing sites were mapped by Vacacaí fishermen, ten of which have irrigation pumps. These sites were considered potential areas of conflict between the two activities analyzed. Due to the size of the study area and the need to demonstrate the elements of analysis in detail, the final map containing this information had to be divided into three parts.